2015
DOI: 10.1080/08998280.2015.11929314
|View full text |Cite
|
Sign up to set email alerts
|

Gastropericardial Fistula as a Delayed Complication of a Nissen Fundoplication

Abstract: A 41-year-old man presented to the emergency department with substernal chest pain and was found to have ST elevations in the inferior leads on his electrocardiogram. An emergent cardiac catheterization did not identify significant coronary narrowing. Computed tomography of the thorax demonstrated a pneumopericardium and a hiatal hernia. The patient had a complicated past surgical history, including a Nissen fundoplication and three additional surgeries for postoperative complications. An esophagram later reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Regardless of the localization of the ST elevation in the initial EKG, these cases were eventually diagnosed using a very similar approach involving a coronary angiogram followed by a CT scan. The diagnosis of pneumopericardium was done retrospectively by radiographic imaging studies in most of the literature-reported cases [1,[6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the localization of the ST elevation in the initial EKG, these cases were eventually diagnosed using a very similar approach involving a coronary angiogram followed by a CT scan. The diagnosis of pneumopericardium was done retrospectively by radiographic imaging studies in most of the literature-reported cases [1,[6][7][8][9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“… 1 – 6 Pneumopericardium on imaging studies is a key finding. 2 , 5 Successful treatment requires rapid diagnosis, hemodynamic resuscitation, antibiotics, and immediate surgical intervention. 1 Nonetheless, mortality estimates are high, ranging between 12% and 85%.…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall complication rate was higher with nonabsorbable mesh (OR = 1.45; 95 % CI 1.24 -1.71; p < 0.01). [9] Doubts about the expediency of routine use of implants in the surgical treatment of PEH are reinforced by reports of complications associated with them: shrinkage, mesh migration [24,107,34], infection (abscesses, fistulas) [33,67], cardiac tamponade, erosion of the aorta [91], esophagus or stomach [75,2], esophageal stenosis [121], severe dysphagia, and fibrotic reaction that may complicate new esophageal surgery [122]. A recent survey of surgeons showed that 21 % and 25 % of respondents diagnosed mesh erosion and esophageal stenosis, respectively [57].…”
Section: T a Tarasov L Y Markulanmentioning
confidence: 99%